A Critical Review on Activity-Based Costing Technique: Analysis of Abundant Countries (Journal of Entrepreneurship and Business, 2022)
Activity-based costing has been identified as an effective costing system that helps the companies in manufacturing and service industry to reduce their cost. Due to the high reliability and accuracy of activity-based costing, without a doubt, activity-based costing had been used and implemented widely by companies in the manufacturing and service industry to replace traditional costing. This is because traditional costing has been considered by many researchers that it is no more reliable and effective to act as a costing system in this constantly changing market conditions, developing technology, and a large number of productions. Furthermore, the activity-based costing system as mentioned just now can provide a lot of benefits to the company which implements it such as providing detailed cost information which can show a clear picture to the management on the costing of their products, which leads to a better decision making as well as improvise the strategic planning of the companies to achieve better profitability and sustainability of the business in the long run.
Keywords: Array; Array; Array